Communication, cohesion and family satisfaction in senior high and high school adolescents. Cienfuegos 2014 - Celia Alfonso Hernández; Anais Marta Valladares González; Lisandra Rodríguez San Pedro; Marina Selín Ganén (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: The family is the instance of intermediation between the individual and society, it constitutes the space par excellence for adolescent identity development, being the first group of socialization and provide the conditions for healthy personality development. Objective: to determine the type of communication, the level of cohesion and the degree of family satisfaction in adolescents who attend senior high and high education centers. Methods: A descriptive study was carried out from January to March 2014 in 62 adolescents from the municipality of Cienfuegos, selected at random stratified by sex. The following techniques were applied: structured interview, questionnaires to measure adolescent-mother communication and adolescent-parent communication, subscale of family cohesion and instrument to measure family satisfaction. Results: 13 and 16-year-old adolescents predominated in medium-sized, nuclear, bigenerational families that are in the extension stage. Positive communication, high cohesion and family satisfaction prevailed in the average adolescents. In late adolescents communication is limited, they have intermediate level of cohesion and are dissatisfied with their families. Conclusions: the average adolescents showed good communication with parents, family unit and satisfaction. In the late adolescents qualitative changes were verified regarding the communication with parents, they did not feel so close to their family and showed little satisfaction.